Persepsi Wisatawan Terhadap Kualitas Pelayanan Pada Objek Wisata Danau Linow di Kota Tomohon - Deisy Andih; Radjab Djamali (PolimdoSains, 2021)
Lake Linow is one of the tourist objects located in Tomohon city and is a favorite tourist attraction visited by tourists both local, national and even international tourists. The topography of Tomohon City, which is flanked by two mountains, namely Mount Lokon and Mount Mahawu, makes this area feel so cool. Beautiful nature with the main display of panoramic mountains and hills. Flowers thrive around this area so that Tomohon gets the nickname City of a Thousand Flowers. One of the leading tourist destinations in this area is Lake Linow, a beautiful lake that exudes the beauty of 3 colors. Located 30 km from the city of Manado or takes about 1 hour drive, Lake Linow can be reached 3 km to the west of Tomohon City. The object of this research is Linow lake tourism object in Tomohon City. This research uses descriptive research quantitative method. The perception of tourists about the quality of service at the Linow Lake tourist attraction in Tomohon City on average is positive